Elaboração de consórcios probióticos bacterianos para uso em cultivo de camarões marinhos (Litopenaeus vannamei) - Abreu, Jade Oliveira (2019)
The massive use of chemicals for pathogen control and nursery fertilization creates strong ecological pressure on areas near shrimp farms and makes the activity environmentally unsustainable. These chemicals released into aquaculture effluents have consequences for the environment beyond the risks to the health of the population and the activity itself. One of the alternatives found to minimize these impacts and optimize production is the use of probiotic agents in shrimp farming. Based on this assumption, the objective of this research was to select between a group of bacteria isolated from the intestinal tract of farmed shrimp, those that presented differential characteristics to improve animal health for application as probiotic consortium in shrimp farming. These bacterial strains were identified by chromosomal DNA sequencing and characterized for antimicrobial susceptibility, virulence potential, stress stability, adhesion and antagonistic activity of the selected strains among themselves and against the pathogens Vibrio harveyi and Vibrio parahaemolyticus. From the results of the phenotypic tests three probiotic consortia were formed and immobilized on calcium alginate micropearls and then lyophilized. The lyophilized probiotic consortia were added to the commercial shrimp diet for use in the in vivo challenge assay against the pathogen V. harveyi. The in vivo test was performed in five groups: one negative control (C1), one positive control (C2) and three treatments with distinct probiotic consortia (T1, T2 and T3). The probiotics were offered to the animals with a feeding rate of 5%, at a concentration of 107 CFU/mL of bacteria. After 30 days of consumption of the probiotic consortia, the animals were exposed to the pathogen Vibrio harveyi via immersion. The animals from treatments T1, T2 and T3 did not present statistically significant difference regarding the average weight, biomass and survival in relation to the control animals. However, regarding the presence of heterotrophic bacteria and Vibrio in the resident and transient microbiota and in the Total Hemocyte Count (THC), the shrimp of the treatments presented greater stability and the most efficient immune response. The three treatments presented different mechanisms of action, T1 treatment was able to colonize the intestinal tract of animals, T2 showed potential to inhibit the pathogen and, as well as T3, to stimulate the innate immune system of shrimps.